DNA Damage and Activation of cGAS/STING Pathway Induce Tumor Microenvironment Remodeling - Shen, Rong; Liu, Disheng; Wang, Xiaoning; Guo, Zhao; Sun, Haonan; Song, Yanfeng; Wang, Degui (Frontiers in Cell and Developmental Biology, 2022)
DNA damage occurs throughout tumorigenesis and development. The immunogenicity of DNA makes it an immune stimulatory molecule that initiates strong inflammatory responses. The cGAS/STING pathway has been investigated as a critical receptor in both exogenous and endogenous DNA sensing to activate the innate immune response. Growing lines of evidence have indicated that activation of the cGAS/STING pathway is critical in antitumor immunity. Recent studies have demonstrated the outstanding advancement of this pathway in tumor-combined immunotherapy; accordingly, increased studies focus on exploration of STING pathway agonists and analogues. However, current studies propose the potential use of the cGAS/STING pathway in tumor initiation and metastasis. Here, we review the molecular mechanisms and activation of the cGAS/STING pathway, and the relationship between DNA damage and this pathway, particularly highlighting the remodeling of immune contexture in tumor environment (TME) triggered by cascade inflammatory signals. A detailed understanding of TME reprogramming initiated by this pathway may pave the way for the development of new therapeutic strategies and rational clinical application.